Ecoliteracy Learning Design with Augmented Reality-Based SETS Approach for Flood Disaster Education - Siva Safitri; Juhadi Juhadi; Ananto Aji (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: : Environmental damage is strongly related to the threat of flood disasters. To reduce the impact of the risk, environmental care behavior and flood disaster education are needed in formal education. The purpose of this study is to apply Ecoliteracy learning design with an Augmented Reality-based SETS approach to increase students' knowledge about environmental care and efforts to reduce the impact of flood risk. Method: This study uses a mixed method of concurrent embedded design; the trial was carried out in one Class XI specialization in geography at State high school 1 Sayung. The research syntax uses the SETS (Science Environment Technology Society) approach with Augmented Reality Ecoliteracy Application media. Results: The results showed that AR Ecoliteracy media has an assessment score percentage of 90.46% with very good criteria, the SETS learning process with AR Ecoliteracy media can make students more interested in learning the material, but in the realm of science still needs support from teachers. The results of the Pre-Test and Post-Test paired sample tests obtained a value of Sig.<0.05. This means that this research design is effective in increasing students' knowledge, caring for the environment and efforts to reduce the impact of flood risk. Novelty: The use of augmented reality media is needed in education, especially with Generation Z. Research using the SETS approach in geography maple has yet to be conducted, so it can be the first step in developing this design.